2014
DOI: 10.5194/acp-14-11525-2014
|View full text |Cite
|
Sign up to set email alerts
|

Denitrification by large NAT particles: the impact of reduced settling velocities and hints on particle characteristics

Abstract: Abstract. Vertical redistribution of HNO 3 through large HNO 3 -containing particles associated with polar stratospheric clouds (PSCs) plays an important role in the chemistry of the Arctic winter stratosphere. During the RECON-CILE (Reconciliation of essential process parameters for an enhanced predictability of Arctic stratospheric ozone loss and its climate interactions) campaign, apparently very large NAT (nitric acid trihydrate) particles were observed by the airborne in situ probe FSSP-100 . Our analysis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 39 publications
(57 reference statements)
0
26
0
Order By: Relevance
“…For NAT clouds Woiwode et al (2014) found indications that aspherical particles might modify the spectral shape of the characteristic spectral NAT feature at 820 cm −1 in balloon-based IR measurements (Fig. 1).…”
Section: Cloud Scenario Databasementioning
confidence: 94%
“…For NAT clouds Woiwode et al (2014) found indications that aspherical particles might modify the spectral shape of the characteristic spectral NAT feature at 820 cm −1 in balloon-based IR measurements (Fig. 1).…”
Section: Cloud Scenario Databasementioning
confidence: 94%
“…As a result of the cold bias, the NAT particles cannot evaporate fast enough to return the nitric acid back to the gas phase around 400 K. Instead, the NAT particles fall out of the stratosphere. However, the sensitivity tests by Woiwode et al [2014] indicate that the renitrification at the lower altitude is not very sensitive to 61 K temperature bias. Instead, the falling velocity of NAT is important for simulating the renitrification of HNO 3 .…”
Section: Denitrification During the 2010-2011 Wintermentioning
confidence: 95%
“…However, the sensitivity tests by Woiwode et al . [] indicate that the renitrification at the lower altitude is not very sensitive to ±1 K temperature bias. Instead, the falling velocity of NAT is important for simulating the renitrification of HNO 3 .…”
Section: Sd‐waccm/carma Simulations Of Pscsmentioning
confidence: 99%
“…13a), probably indicating sedimentation of NAT and permanent denitrification. However, since Woiwode et al (2014) have reported the presence of NAT with larger apparent sizes compared to compact spherical particles and with concomitant reduced settling rates, we must also consider the possibility that the NAT radius grew larger and subsequently evolved into sub-visible NAT. Höpfner et al (2009), and even with longer-term averaging, over the entire May-October period, Spang et al (2016) concluded that MIPAS has higher sensitivity to PSCs since, for the cases where CALIOP detects no cloud, about 60 % correspond to cloudy scenes for MIPAS.…”
Section: Interannual Variations In the Early Antarctic Psc Seasonmentioning
confidence: 99%
“…The morphology of NAT particles is still an open question, as is the compactness of the particles Woiwode et al, 2014Woiwode et al, , 2016. Light scattering studies have repeatedly shown that detailed particle morphology cannot be deduced from the depolarization; e.g., Nousiainen et al (2012) investigated simple and complex shapes with size parameters (ratio of the particle circumference to the wavelength) in the range 2-12 and real refractive indices in the range 1.55-1.603 representative of silicate particles, and noted similar depolarization ranges for the fifteen different shapes (regular and irregular) that were analyzed.…”
Section: Sts/nat Mixturesmentioning
confidence: 99%